Cohort profile: the Hlabisa pregnancy cohort, KwaZulu-Natal, South Africa - Chetty, Terusha; Thorne, Claire; Tanser, Frank; Bärnighausen, Till; Coutsoudis, Anna (BMJ open, 2016)
Purpose The Hlabisa pregnancy cohort was established to evaluate the effectiveness of prevention of mother-to-child transmission (PMTCT) guideline revisions. The objectives of the Hlabisa pregnancy cohort are to: (1) provide cohort-level information on maternal health up to 6 weeks postpartum in a high HIV prevalence setting; and to (2) evaluate aspects of PMTCT care that have policy relevance. - Participants The pregnancy cohort is located in primary health clinics in the Hlabisa subdistrict of rural KwaZulu-Natal, South Africa. Baseline data collection between 2010 and 2014 has been completed with the enrolment of 25 608 pregnancies; age ranged from 15-49 years. Pregnant women were assessed during routine antenatal visits: first visit, follow-up 1 week later, 32 weeks (HIV test), infant delivery and 6 weeks postpartum. Demographic, pregnancy, clinical, laboratory and HIV data were collected through Department of Health interviews, laboratory tests and routine data linkage. Treatment data for HIV-infected pregnant women were linked to the Africa Centre Hlabisa HIV Treatment and Care Programme for detailed antiretroviral therapy (ART) history and laboratory tests. - Findings to date The proportion of women initiated on ART post-2013 were higher (n=437; 100%) than pre-2013 (n=768; 84.2%). The proportion of women in care at 6 weeks (73.8%) was also higher post-2013 relative to earlier years (58.5%). The majority of HIV-infected pregnant women were either on lifelong ART or ART prophylaxis; pre-2013, ∼ 9.6% of women were not on any ART. Pregnancy viral load monitoring was inadequate. - Future plans This cohort will be used to: (1) determine HIV acquisition risk during pregnancy and postpartum; (2) determine the effect of HIV and ART on birth outcomes; (3) examine the effect of pregnancy on virological response to ART; and (4) characterise the effect of sequential pregnancies on access to clinical care, response to prolonged ART and birth outcomes.
Accepted 5 August 2016
Gesehen am 30.04.2020